Harapan Orang Tua Memberi Nama Anak di Daerah Mandailing - Novita Trianto Hasibuan (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
The name is the language of human communication. Therefore, the naming of a child by a parent will vary from one parent to another. The child's name is a language that represents the language of the mind of parents associated with the environment. Each parent has their own reasons and expectations of the names given to their children. Batak communities have distinctive names. Name according to the parents, can bring good luck and is also known where someone is coming. The results of this study are expected to know and the authors draw conclusions from the study of the relationship name sociolinguistic children with parental expectations. This research is helpful for those who want to review the names of people, especially in the area Mandailing. Based on these results, it appears that the names of the Mandailing show close relationship between the child's name and the hope of his parents as a vagabond. Viewing from the meaning of the name of each student indicates that exalts the name meaning, goodness, valor, tenderness, charm, servitude and obedience. The parents tried to give the names of their children with the best name in their opinion.